Orcein and Fluorescent Banding Analysis of Two Floral Types of Catharanthus Roseus L. (Dhaka University Journal of Biological Sciences, 2020)
Two floral types of Catharanthus roseus L. viz. pink and white were studied through differential staining with orcein, CMA and DAPI for cytogenetical characterization and to assist towards updating their taxonomical status and evaluating chromosomal diversity between them. "Simple Chromocenter Type" of interphase nuclei was observed with some darkly stained small heterochromatic regions throughout the nuclei. Most of the prophase chromosomes of Catharanthus roseus (pink and white) were "Continuous Type" and a few were "Gradient Type". Although these two floral types possessed 16 metacentric chromosomes in somatic cells, they showed variation in fluorescent banding pattern considering the modification of GC- and AT-rich repetitive segments. Taking into account all the parameters of both the floral types of C. roseus showed strict symmetric karyotype as well as primitive nature. Therefore, the combined data of differential staining provide information to make comments on their chromosomal status with cytogenetical characterization and also create a baseline for future research.Dhaka Univ. J. Biol. Sci. 29(2): 219-227, 2020 (July)